Updating the Use of Methods in Learning to Speak for University Students: A Literature Review Study - Kusmadi Sitohang; Andoyo Sastromiharjo; Alfianika, Ninit (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
This research is motivated by the importance of speaking skills for students. This is proven by the existence of courses or speaking material that students must master. The reality is, there are still students who have problems or lack skills in speaking. So it is very important for educators to improve students' speaking skills. Therefore, this research aims to recommend learning methods that have been proven to improve speaking skills. This type of research is a literature review study. The instrument used in this research is a documentation study. Articles collected via Google Scholar, ResearchGate, and Sciencedirect search engines. The data sources in this research amounted to 15 articles, 8 articles obtained from Google Scholar, 5 articles from Researchgate, and 2 Scopus articles. The data sources in this research start from 2017 to 2023. Data analysis was carried out using descriptive analysis, namely describing the articles found in accordance with the research objectives. The research results showed that there are 6 learning methods that have been proven to improve students' speaking skills, namely the debate method, Numbered Head method, project-based learning method, based learning method, jigsau method, and stand up category method; 4 learning models that have been proven to improve students' speaking skills, namely the mind mapping learning model, service project-based learning model, Auditory Intellectually Repetition (AIR) model, and Information learning model; 1 learning strategy that has been proven to improve students' speaking skills. based on collective reflection. So, very few scientific publications discuss learning methods that have been used to improve speaking skills among students.